HIGHLY SPESIFIC BACILLUS CEREUS-PHAGES ISOLATED FROM HOSPITAL WASTEWATER IN BANYUMAS REGENCY - Anwar Rovik; Saefuddin ‘Aziz; Hendro Pramono (UNEJ e-Proceeding, 2016)
Bacillus cereus is pathogenic bacteria that frequently contaminate food by producing entero and emetic toxins. B. cereus had shown resistance to various antibiotics. An alternative to control B. cereus is the use of bacteriophages. This study aims to determine whether bacteriophages isolated from hospital wastewater in Banyumas Regency is highly specific to B. cereus. The research was carried out descriptively through isolation, purification, enumeration, specificity, effectivity, and host-lysing rate test. B. cereus phages were isolated from hospital wastewater in Banyumas Regency with various titer, i.e. 108-109 PFU.ml-1. The PKRW-1, PKCL-1, PKSR-2, RSBMS-2, RSBMT-1, RSAJP-1, RSAJP-2, RSAJK-2, RSAJE-1, and RSAJE-3 phages have a great specificity and effectivity of infection to B. cereus. Total of 7 isolated phages have a fast host-lysing rate by the 2nd hour of incubation.